2000
DOI: 10.1080/713803721
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Regulation by Oxidative Stress in Different Cell Types

Abstract: Focal adhesion kinase (FAK) is a tyrosine kinase ubiquitously expressed in cells. It was initially shown to be the initiator of focal adhesion formation in adherent cells, after its binding to integrins which induce its autophosphorylation. However, it can be also activated by a great variety of other stimuli able to act on different intracellular signaling. Reactive oxygen species (ROS), which have been shown to act as external or internal cell stimuli, induce tyrosine phosphorylation of FAK. Its autophosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Stimulation of FAK phosphorylation has been demonstrated in response to mechanical stretch in cardiac myocytes (50,55,56) and fibroblasts (64) and in response to shear stress (30) or stretch (2) in endothelial cells. FAK phosphorylation is also increased in endothelial cells in response to oxidative stress (7,60,61). Neither high stretch (MV) nor hyperoxia (HO) alone affected FAK phosphorylation in our studies, suggesting tight regulation of FAK signaling under these conditions in vivo.…”
Section: Discussionmentioning
confidence: 42%
“…Stimulation of FAK phosphorylation has been demonstrated in response to mechanical stretch in cardiac myocytes (50,55,56) and fibroblasts (64) and in response to shear stress (30) or stretch (2) in endothelial cells. FAK phosphorylation is also increased in endothelial cells in response to oxidative stress (7,60,61). Neither high stretch (MV) nor hyperoxia (HO) alone affected FAK phosphorylation in our studies, suggesting tight regulation of FAK signaling under these conditions in vivo.…”
Section: Discussionmentioning
confidence: 42%
“…Several mechanisms of ROS regulation of cancer cell migration have been proposed; most of these involve alterations of cellular cytoskeleton and adhesion molecules. For instance, ROS have been reported to regulate integrin (13,14), small GTPase Rho family proteins (15,16), focal contact-forming proteins (13,17), and extracellular matrix-degrading enzymes such as matrix metalloproteinases (14,18,19). Caveolin-1 (Cav-1) is an essential structural protein component of the plasma membrane microdomains called caveolae.…”
mentioning
confidence: 99%
“…To our knowledge, the ROS dependent regulation of FAK phosphorylation has not been examined in the VSMC. Ben Mahdi et al (2000) have suggested that ROS may induce FAK phosphorylation through phosphoinositide 3-kinase (PI3-K). Interestingly, we have recently demonstrated that the aortic content and activity of phosphatase and tensin homolog (PTEN), a negative regulator of PI3K signaling, is upregulated with aging in the F344/NXBN.…”
Section: Discussionmentioning
confidence: 99%
“…The factors, which influence the activation of FAK are diverse, as increases in FAK phosphorylation have been linked to a number of different stimuli including integrin engagement, growth factor stimulation, bioactive lipids, and elevated reactive oxygen species (ROS) (Ilic et al 1997;Ben Mahdi et al 2000). Given these data and previous findings from our laboratory demonstrating that ROS levels are increased in the aged F344XBN aorta (Rice et al 2006), it is intriguing that the extent of FAK phosphorylation (Tyr 925) is diminished with aging (Fig.…”
Section: Discussionmentioning
confidence: 99%